2022
DOI: 10.1055/a-2000-8406
|View full text |Cite
|
Sign up to set email alerts
|

PDE5A: Key Enzyme to Overcome Platelet Inhibition

Abstract: No Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The study revealed that diminished VWF synthesis/secretion and increased VWF clearance play contributing roles. 83 Importantly, Bourne et al 84 alerted to CLEC-2's distinct role in mouse and human platelets. While CLEC-2 is vital for thrombus growth in mice, it appeared to be less crucial for human platelet thrombus formation under arterial shear, raising key questions about CLEC-2's biological role in mice versus humans.…”
Section: Getting To the Heart Of The Mattermentioning
confidence: 99%
“…The study revealed that diminished VWF synthesis/secretion and increased VWF clearance play contributing roles. 83 Importantly, Bourne et al 84 alerted to CLEC-2's distinct role in mouse and human platelets. While CLEC-2 is vital for thrombus growth in mice, it appeared to be less crucial for human platelet thrombus formation under arterial shear, raising key questions about CLEC-2's biological role in mice versus humans.…”
Section: Getting To the Heart Of The Mattermentioning
confidence: 99%